Molecular geometry regulation of bay-phenyl substituted perylenediimide derivatives with bulky alkyl chain for use in organic solar cells as the electron acceptor. (January 2017) - Yi, Jinduo; Wang, Junkai; Lin, Yi; Gao, Wei; Ma, Yuchao; Tan, Hongwei; Wang, Hongyu; Ma, Chang-Qi
Abstract: Perylenediimide derivatives (PDI) are among the most promising non-fullerene electron acceptor materials for use in organic solar cells. However, owing to the intensive intermolecular interactions, the non-functionalized PDI molecules showed high tendency of aggregation in solid film, which leads to poor device performance. In this paper molecular geometry of PDI derivatives was finely tuned by introducing a bulky isopropyl group on the bay -phenyl unit, and influences of such a bulky alkyl group on the optical and electrochemical properties were systematically studied. Results indicated that the bulky isopropyl group on the para - and meta -position of the bay -phenyl group has negligible influence on the twist angle between the PDI core and the bay -phenyl unit, and these two compounds (4-iPP-PDI and3-iPP-PDI ) have similar molecular properties. However, large steric hindrance of the ortho -isopropyl group causes a large twist between the PDI core and the bay -phenyl unit, which leads to conjugation break, and consequently to a blue-shifted absorption spectrum and an increased optical band gap for the final PDI compound (2-iPP-PDI ). Polymer solar cells using these bay -phenyl functionalized PDIs as the electron acceptor were fabricated and tested. And the meta -substituted PDI compound3-iPP-PDI show the better device performance than the para - and ortho -substituted compounds (4-iPP-PDI and2-iPP-PDI ), which was ascribed to the proper nano-scale phase separation and high electron mobility of the blended film. The current results proved that molecular geometry of PDI derivatives can be finely regulated through introducing bulky alkyl side chain on the bay -substitution group to achieve a balanced property of crystallinity and electron mobility. Graphical abstract: Highlights: Three isopropylphenyl substituted asymmetric PDI derivatives were reported. Effects of isopropyl chain position of PDIs on property and PV performance were studied. These PDIs showed similar LUMO energy levels to PC61 BM. The meta -substituted 3-iPP-PDIs showed the best performance in polymer solar cells.